Albofungin and chloroalbofungin: antibiotic crystals with 2D but not 3D isostructurality. Issue 12 (25th November 2020) - Ye, Wenkang; She, Weiyi; Sung, Herman H.-Y.; Qian, Peiyuan; Williams, Ian D.
Abstract : The crystal structures of the potent antibiotics albofungin and its chlorinated analogue chloroalbofungin have been determined after their isolation from Streptomyces chrestomyceticus . The N ‐aminoquinolone molecular arrangement, regiochemistry of chloro substitution and absolute stereochemistry at three chiral centres of the xanthone rings (10 S, 13 R and 19 R ) are confirmed and their supramolecular assemblies are compared, which show 2D rather than 3D isostructurality. Abstract : The potent antibiotics albofungin [systematic name: (1 S, 4 R, 8a R )‐13‐amino‐1, 15, 16‐trihydroxy‐4‐methoxy‐12‐methyl‐3, 4, 8a, 13‐tetrahydro‐1 H ‐xantheno[4′, 3′, 2′:4, 5][1, 3]benzodioxino[7, 6‐ g ]isoquinoline‐14, 17(2 H, 9 H )‐dione, C27 H24 N2 O9, 1 ] and its chlorinated analogue chloroalbofungin (the 11‐chloro analogue, C27 H23 ClN2 O9, 2 ) have been crystallized following their isolation from the bacterial strain Streptomyces chrestomyceticus and their structures determined by single‐crystal X‐ray diffraction. The novel N ‐aminoquinolone molecular arrangement shows N—N bond lengths of 1.4202 (16) and 1.424 (2) Å in 1 and 2, respectively. The regiochemistry of chloro substitution in the A ‐ring is para to the quinolone O atom, with a C—Cl bond length of 1.741 (2) Å. The absolute stereochemistry at three chiral centres of the xanthone rings ( i.e. 10 S, 13 R and 19 R ) is confirmed. Both compounds crystallize in chiral Sohncke space groups consistent with enantiopurity, but are not fully isostructural. A preserved supramolecular construct (SC) confers two‐dimensional (2D) isostructurality, but the SC self‐associates via either a twofold screw operation in 1, giving a monoclinic P 21 structure, or a twofold rotation in 2, affording a monoclinic C 2 structure with a doubled unit‐cell axis.